PERAN MUHAMMADIYAH DALAM MENANGGULANGI KERJA MISIONARIS (STUDI KASUS DI MAGELANG) - Yasri, Akhsani Sholihati; Arqam, Muhammad Lailan (Jurnal Dakwah Tabligh, 2022)
This article aims to find out the history of Christianity in Magelang and analyze the role of the Muhammadiyah organization in overcoming Christianity. Research-based on interviews and assessment of reliable sources with qualitative methods. This study can be concluded that the spread and process of Christianization occurred slowly from communication and entered into the layers of society and ultimately changed the mindset of the local population there, some returned to Islam and some did not return to Islam. Muhammadiyah’s role in tackling Christianity is embracing the community, starting from recitation studies, schools, and Islamic boarding schools, to campuses and the Science Council and developing the world of goodness in the world of scholarship, religious knowledge, providing service centers for indigenous peoples that create comfort and awareness and make da’wah to people who feel poverty and persuasion by Islam to make the return of many people to the right path.